Impact of COVID-19 on animal health care services, coping practices and associated financial loss to livestock farmers in Karnataka - Govindaraj, G.; Shanabhoga, M.B.; Swamy, H.M.; Naveenkumar, G.S.; Nagalingam, M.; Mahantheshwara, B.; Balamurugan, V.; Shome, B.R.; Rahman, Habibar (Indian Council of Agricultural Research, 2022)
The study assessed the impact of COVID-19 associated lockdowns on animal health services, coping practices, and financial loss to livestock farmers in Karnataka. A cross-sectional survey among 170 livestock farmers and 24 field veterinarians working in the study jurisdiction were interviewed using a structured questionnaire. Descriptive statistics and repeated ANOVA were employed to asses the impact of COVID-19 lockdown. The results revealed a significant difference in the number of cases attended at different periods of lockdowns and among the veterinarians, with a decline in the number of cases attended across the species of pets (54.9%) followed by goats (35.3%), sheep (29.1%), cattle (25.5%) and buffalo (21.6%) during the lockdown. The mode of veterinarian contact through phone calls (80%) and WhatsApp (46.7%) increased significantly and veterinarian visits decreased by 27.3% and farmers' visits to veterinary hospitals decreased by 61.9% during lockdown. The livestock farmers' welfare schemes were abstracted by lockdown and the vaccine administration against diseases like PPR, ET, and HS per veterinarian declined in sheep and goats. However, targeted vaccination against FMD in cattle was found achieved. The COVID-19 and associated lockdown affected the livestock farmers in multiple dimensions. Hence, to cope with lockdown-like situations, it is recommended to engage trained personnel, practitioners, and Non-Governmental Organisations (NGOs) associated with animal health care services to provide uninterrupted health care services to livestock farmers.